Skeptical Theism, Soul Making, and Kant’s Practical Response to the Problem of Evil - Pasternack, Lawrence (Con-Textos Kantianos. International Journal of Philosophy, 2026)
This paper examines Kant’s distinctive response to the Problem of Evil (PE) and situates it in relation to contemporary debates on Skeptical Theism. Standard approaches to PE assume two independent premises—the existence of God and the existence of evil—and then attempt reconciliation through doctrinal theodicies or epistemic humility. Kant, by contrast, reconfigures PE through his Moral Argument and “Authentic Theodicy,” grounding belief in God in the moral need to resist despair before suffering and injustice. This practical theodicy neither denies evil nor speculatively explains it, but frames faith as a necessary condition for sustaining moral resolve. In doing so, Kant avoids the Symmetry Objection often raised against Skeptical Theism and offers a response that is neither fideistic nor doctrinal but rooted in the demands of practical reason. The paper argues that this Kantian strategy provides a distinctive and underexplored framework for addressing PE within philosophy of religion.